Augmenting a guitar with its digital footprint - Benford, Steve; Hazzard, Adrian; Chamberlain, Alan; Xu, Liming (2015)
We explore how to digitally augment musical instruments by connecting them to their social histories. We describe the use of Internet of Things technologies to connect an acoustic guitar to its digital footprint – a record of how it was designed, built and played. We introduce the approach of crafting interactive decorative inlay into the body of an instrument that can then be scanned using mobile devices to reveal its digital footprint. We describe the design and construction of an augmented acoustic guitar called Carolan alongside activities to build its digital footprint through documented encounters with twenty-seven players in a variety of settings. We reveal the design challenge of mapping the different surfaces of the instrument to various facets of its footprint so as to afford appropriate experiences to players, audiences and technicians. We articulate an agenda for further research on the topic of connecting instruments to their social histories, including capturing and performing digital footprints and creating personalized and legacy experiences.